Plate removal following orthognathic surgery. Issue 9 (November 2015) - Little, Mhairi; Langford, Richard Julian; Bhanji, Adam; Farr, David
Abstract: The objectives of this study are to determine the removal rates of orthognathic plates used during orthognathic surgery at James Cook University Hospital and describe the reasons for plate removal. 202 consecutive orthognathic cases were identified between July 2004 and July 2012. Demographics and procedure details were collected for these patients. Patients from this group who returned to theatre for plate removal between July 2004 and November 2012 were identified and their notes were analysed for data including reason for plate removal, age, smoking status, sex and time to plate removal. 3.2% of plates were removed with proportionally more plates removed from the mandible than the maxilla. 10.4% of patients required removal of one or more plate. Most plates were removed within the first post-operative year. The commonest reasons for plate removal were plate exposure and infection. The plate removal rates in our study are comparable to those seen in the literature.